Change by Activism: Insurgency, Autonomy, and Political Activism in Potosí-Jerusalén, Bogotá, Colombia - Usubillaga, Juan (2022)
Cities today face a context in which traditional politics and policies struggle to cope with increasing urbanisation rates and growing inequalities. Meanwhile, social movements and political activists are rising up and inhabiting urban spaces as sites of contestation. However, through their practices, urban activists do more than just occupy spaces; they are fundamental drivers of urban transformation as they constantly face—and contest—spatial manifestations of power. This article aims to contribute to ongoing discussions on the role of activism in the field of urban design, by engaging with two concepts coming from the Global South: insurgency and autonomy. Through a historical account of the building of the Potosí-Jerusalén neighbourhood in Bogotá in the 1980s, it illustrates how both concepts can provide new insight into urban change by activism. On the one hand, the concept of insurgency helps unpack a mode of bottom-up action that inaugurates political spaces of contestation with the state; autonomy, on the other hand, helps reveal the complex nature of political action and the visions of urban transformation it entails. Although they were developed at the margins of conventional design theory and practice, both concepts are instrumental in advancing our understanding of how cities are shaped by activist practices. Thus, this article is part of a broader effort to (re)locate political activism in discussions about urban transformation, and rethink activism as a form of urban design practice.